Cancer immunogenic cell death via photo-pyroptosis with light-sensitive Indoleamine 2, 3-dioxygenase inhibitor conjugate. (November 2021) - Lu, Yang; Xu, Feng; Wang, Yang; Shi, Chao; Sha, Yuzhuo; He, Guangli; Yao, Qichao; Shao, Kun; Sun, Wen; Du, Jianjun; Fan, Jiangli; Peng, Xiaojun
Abstract: Immune checkpoint blockade (ICB) therapy currently considered as to be effective way to cure cancer in clinic. However, the insufficient tumor immunogenicity and the immunosuppressive tumor microenvironment always result in diminished efficacy of immunotherapy. Herein, we report the synthesis of an organic photo-immune activator NBS-1MT, the combination of photosensitizer and Indoleamine 2, 3-dioxygenase (IDO) inhibitor effectively stimulates lysosomes oxidative stress the releases inflammatory cytokines. This process triggers pyroptosis for the considerable immunogenic cell death (ICD) while reversing suppressive tumor microenvironment. The photo-immune drug shows outstanding potential to activate caspase-1and then remove gasdermin-D (GSDMD), which could stimulate pyroptosis and also inhibit the tumor growth successfully in both primary and distant tumor. Furthermore, pyroptosis activated by photodynamic therapy (PDT) promotes the immune related factors release, and enhance the intratumoral infiltration of cytotoxic T lymphocytes (CTLs) with the induction of ICD of tumor cells and the cascaded synergize with IDO inhibitor, so the general antitumor immune response could be strengthened effectively. Our research confirms that the use of NBS-1MT is a promising strategy to boost the immune response and eventually to inhibit tumor growth.